Analisis Kepatuhan Pajak Penghasilan Terhadap Penghasilan Negara di Indonesia - Carrens; Candy Angkasa; Federick Daffi Tasmin; Jose Neilson; Jonathan Wijaya; Sukardi Hadiwinata (Jurnal Riset Bisnis dan Ekonomi Digital, 2025)
DJP as the tax regulator in Indonesia always strives to increase state revenue as the foundation for the running of the country by improving tax compliance. Taxpayer compliance supporting the increase in annual tax revenue, so the DJP provided a breakthrough in the form of digitizing tax reporting by moving the service and reporting system online, then in 2017 a system was created to improve tax services and reporting in the form of e-form as a tax return reporting facility which is expected to facilitate reporting and increase the level of tax compliance. The purpose of this study is to determine whether the digitalization factor in the form of e-form can have an impact on taxpayer compliance. The research method uses a descriptive qualitative approach. The data used in the study were taken from literature studies that took several reference journal articles. The study results can be concluded that e-form has a better significant effect on increasing tax compliance.